General Electric and GE Capital - Varma, Jayanth R.; Jacob, Joshy (London : Indian Institute of Management, Ahmedabad, 2011)
The case focuses on General Electric during the financial crash of 2008 and how this caused problems for General Electric as a whole and more specifically General Electric Capital, wholly-owned financial services subsidiary of General Electric.GE and GE Capital faced the following immediate and interrelated challenges with the onset of the uncharacteristic financial crisis: (i) tackling the deep liquidity problems arisen due to its overreliance on short-term funding, (ii) addressing the solvency issues created due to its high leverage and asset quality deterioration, and (iii) maintaining the market expectations about an investment-grade borrower. In the medium-term, it might also have to restructure its combined industrial-financial portfolio to suit the evolving business and financial environment.
Originally published in Varma, J. R., & Jacob, J. (2011). General Electric and GE Capital. F&A0491. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; General Electric Company -- Finance; Electric utilities -- United States -- Finance